The logistics and supply chain toolkit - Richards, Gwynne; Grinsted, Susan (Kogan Page, 2016)
"The Logistics and Supply Chain Toolkit provides practical, take-away tools for warehouse, inventory and transport managers to apply to the day-to-day challenges of logistics and supply chain management. This book offers applicable solutions to some of the most frequently encountered problems of the industry. The 2nd edition has been thoroughly revised to ensure that all research is updated to reflect the latest innovations in technology and processes. The tools have been revised to ensure the utmost relevance, and a collection of new tools has been added to ensure that the book is relevant and applicable in light of the most recent changes to the sector. The aim of The Logistics and Supply Chain Toolkit is to provide today's managers with a toolbox of practical ideas and information to help them in their day-to-day work. It explains a number of the major management tools and suggests areas within supply chain and logistics where they can be applied. The tools have been put into chapters, including supply chains, warehousing, transport and inventory"--Resumé vydavatele
Keywords: logistika (management); řízení zásob; business logistics; inventory control; příručky; handbooks, manuals, etc